CONSTRUCTING A SCALE OF DUAL THINKING SOURCES FOR PHYSICAL EDUCATION TEACHERS AND ITS RELATIONSHIP TO TIME MANAGEMENT IN PHYSICAL EDUCATION LESSONS IN IRAQ FOR ACADEMIC YEAR 2025-2024 - Al-Krizi, Maitham Mutair Hamidi (Holistic Journal of Sport Education, 2025)
The research aims to build a scale of sources of binary thinking for some physical education teachers and instructors in the Republic of Iraq and a scale of time management (prepared by the researcher) and to find the relationship between them. The descriptive approach was used with the sample method, and the exploratory study was applied to a sample of ( 29 ) male and female teachers, and the main study was applied to a sample of ( 300 ) male and female teachers and appropriate statistical treatments were used on ( 6 ) sources (anxiety, negative emotional response, professional pressures, decision-making, overgeneralization, selective abstraction) that represent the main sources of the binary thinking scale, which consists of ( 36 ) phrases divided among those sources, with ( 6 ) phrases for each source, and the time management scale, which consists of ( 30 ) phrases, for the purpose of finding the relationship between them. The researcher concluded that the sources can be used for the scale of binary thinking for physical education teachers and instructors, with the exception of the source of decision-making, as there a statistically significant relationship, and the source of selective abstraction, due to the presence of an inverse, non-significant relationship. We recommend that the following be used: By studying other sources related to dual thinking for physical education teachers and instructors, to determine the importance of these sources in identifying the level of thinking among teachers and instructors. We also recommend holding guidance, educational and evaluation courses to help them develop their scientific, cultural and social capabilities.